Early Blindness Results in Developmental Plasticity for Auditory Motion Processing within Auditory and Occipital Cortex - Jiang, Fang; Stecker, G. Christopher; Boynton, Geoffrey M.; Fine, Ione (Frontiers in Human Neuroscience, 2016)
Early blind subjects exhibit superior abilities for processing auditory motion, which are accompanied by enhanced BOLD responses to auditory motion within hMT+ and reduced responses within right planum temporale (rPT). Here, by comparing BOLD responses to auditory motion in hMT+ and rPT within sighted controls, early blind, late blind, and sight-recovery individuals, we were able to separately examine the effects of developmental and adult visual deprivation on cortical plasticity within these two areas. We find that both the enhanced auditory motion responses in hMT+ and the reduced functionality in rPT are driven by the absence of visual experience early in life; neither loss nor recovery of vision later in life had a discernable influence on plasticity within these areas. Cortical plasticity as a result of blindness has generally be presumed to be mediated by competition across modalities within a given cortical region. The reduced functionality within rPT as a result of early visual loss implicates an additional mechanism for cross modal plasticity as a result of early blindness - competition across different cortical areas for functional role.